Congenital Extrahepatic Portosystemic Shunts: Spectrum of Findings on Ultrasound, Computed Tomography, and Magnetic Resonance Imaging - Pankaj Gupta; Anindita Sinha; Kushaljit Singh Sodhi; Anupam Lal; Uma Debi; Babu R. Thapa; Niranjan Khandelwal (Radiology Research and Practice)
Congenital extrahepatic portosystemic shunt (CEPS) is a rare disorder characterised by partial or complete diversion of portomesenteric blood into systemic veins via congenital shunts. Type I is characterised by complete lack of intrahepatic portal venous blood flow due to an end to side fistula between main portal vein and the inferior vena cava. Type II on the other hand is characterised by partial preservation of portal blood supply to liver and side to side fistula between main portal vein or its branches and mesenteric, splenic, gastric, and systemic veins. The presentation of these patients is variable. Focal liver lesions, most commonly nodular regenerative hyperplasia, are an important clue to the underlying condition. This pictorial essay covers imaging characteristics in abdominopelvic region.